DETERMINING THE EFFECTIVENESS OF USE OF MIXED INSECTICIDES AGAINST COTTON BALL BOLLOW (Scientific journal of the Fergana State University, 2024)
Deltaphos 36% e.e., Progress Plus 44% e.e., Aycon Mix, 20% s.e., Duet, 55% e.e. and one of the main goals of the experiment is to study the biological effectiveness obtained when used in a loosened form. Periods